Forkhead Box O1 Is Present in Quiescent Pituitary Cells during Development and Is Increased in the Absence of p27(Kip1) - Majumdar, Sreeparna (Public Library of Science, 2012)

(untitled)
Congenital pituitary hormone deficiencies have been reported in approximately one in 4,000 live births, however studies reporting mutations in some widely studied transcription factors account for only a fraction of congenital hormone deficiencies in humans. Anterior pituitary hormones are required for development and function of several glands including gonads, adrenals, and thyroid. In order to identify additional factors that contribute to human congenital hormone deficiencies, we are investigating the forkhead transcription factor, FOXO1, which has been implicated in development of several organs including ovary, testis, and brain. We find that FOXO1 is present in the nuclei of non-dividing pituitary cells during embryonic development, consistent with a role in limiting proliferation and/or promoting differentiation. FOXO1 is present in a subset of differentiated cells at e18.5 and in adult with highest level of expression in somatotrope cells. We detected FOXO1 in p27(Kip1)-positive cells at e14.5. In the absence of p27(Kip1) the number of pituitary cells containing FOXO1 is significantly increased at e14.5 suggesting that a feedback loop regulates the interplay between FOXO1 and p27(Kip1).